Foliar uptake of atmospheric nitrate by two dominant subalpine plants: insights from in situ triple‐isotope analysis. Issue 4 (20th March 2019) - Bourgeois, Ilann; Clément, Jean‐Christophe; Caillon, Nicolas; Savarino, Joël
Summary: The significance of foliar uptake of nitrogen (N) compounds in natural conditions is not well understood, despite growing evidence of its importance to plant nutrition. In subalpine meadows, N‐limitation fosters the dominance of specific subalpine plant species, which in turn ensures the provision of essential ecosystems services. Understanding how these plants absorb N and from which sources is important in predicting ecological consequences of increasing N deposition. Here, we investigate the sources of N to plants from subalpine meadows with distinct land‐use history in the French Alps, using the triple isotopes (Δ 17 O, δ 18 O, and δ 15 N) of plant tissue nitrate (NO3 − ). We use this approach to evaluate the significance of foliar uptake of atmospheric NO3 − (NO3 − atm ). The foliar uptake of NO3 − atm accounted for 4–16% of the leaf NO3 − content, and contributed more to the leaf NO3 − pool after peak biomass. Additionally, the gradual 15 N enrichment of NO3 − from the soil to the leaves reflected the contribution of NO3 − atm assimilation to plants' metabolism. The present study confirms that foliar uptake is a potentially important pathway for NO3 − atm into subalpine plants. This is of major significance as N emissions (and deposition) are predicted to increase globally in the future. Abstract : See also the Commentary on this article by Soper, 223 : 1687–1689 .